Is there under-provision of training? - Brunello, Giorgio [Verfasser]; De Paola, Maria [Verfasser] (My University, 2009)
"This paper reviews both the theoretical underpinnings and the empirical evidence in support of the under-provision of general training. In spite of many theoretical reasons for the realization of inefficient levels of training, it is difficult to find convincing empirical evidence. Taking as a starting point the large empirical literature showing that employers provide and pay for general training, we argue that, if firms invest in general training, important evidence on under-provision can be obtained by looking at the relationship between investment in training and turnover. Using the 7 waves (1995-2001) of the European Community Household Panel (ECHP) for 12 European countries, we find a negative but not statistically significant relationship between training and turnover. We conclude that, at the current state of the knowledge, it is difficult to justify training policies widespread in many European countries using efficiency arguments." (Autorenreferat, BIBB-Doku)
Keywords: S 4.3.6 Human Capital; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; I 2.2 Europa; Bildungsinvestition; Humankapital; Kosten-Nutzen-Relation; Bildungsökonomie; Europa